THE EFFECTIVENESS OF QUILLBOT ROLE IN GRAMMAR MODIFICATION FOR TENTH GRADE IN ENGLISH WRITING AT SMAN 1 LOCERET NGANJUK - Suhesti Wulandari; Henny Roesellaningtias (Universitas PGRI Mpu Sindok, 2026)
This study aims to analyze students' writing abilities before and after using Quillbot and to determine significant differences in their grammar modification skills. The study uses a quantitative approach with a quasi-experimental design. Data were collected through writing tests administered before and after using Quillbot, and then analyzed using statistical analysis and a paired sample t-test in IBM SPSS Statistics 25. The results showed that the average pre-test score of 53.97 increased to 81.4 on the post-test. The t-test yielded a Sig. (2-tailed) value of 0.000 < 0.05, indicating a significant difference between students' writing abilities before and after using Quillbot. Thus, Quillbot has been proven effective in enhancing students' writing skills through improved grammar modification.